Oral Presentations Abstracts: THE TRANSFER OF KNOWLEDGE IN A TRUSTWORTHY DOCTOR-PATIENT INTERACTION: A PHILOSOPHICAL PROBLEM - CONSOLANDI, Monica (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 The effectiveness of medical evidence is largely dependent on the ability to communicate that evidence to the science-users, mostly patients. Like in many fields of science, also in medicine trust is one of the most important components of doctor-patient interaction. Cultivation of patient trust is, in turn, primarily a linguistic activity, subject to linguistic norms and conventions. Doctor-patient interaction has been at the core of a growing discussion during the past few years, especially in the context of innovations in evidence-based methods and related to the applicability of clinical guidelines derived from those methods. In Italy, this debate resulted in a recent law (n.219/2017), which declares that “the care and trusting relationship between doctor and patient which is based on the informed consent is promoted and enhanced” (art.1) and that “the time of the communication between doctor and patient is a time of care” (art.8). This new kind of perspective on communication between physicians and patients has led to several questions, above all (i) what is the best definition of trust? and (ii) how achieve a trusting relationship? According to a strictly philosophical point of view, it implies how to successfully communicate imperfect evidence and risk to patients who are in a position of epistemic asymmetry with respect to the doctors; it is problematic because it involves a transfer of complex knowledge of risks and uncertainties from experts to laypeople. The paper investigates the difficulties in communicating medical evidence associated with risk and uncertainties of diagnosis and treatment.